Comportamiento, glándulas accesorias y centros neuroendocrinos en machos de dos especies de Canthon (Coleoptera: Scarabaeinae) - Martínez M., Imelda; Cruz Rosales, Magdalena (Instituto de Ecología, A.C., 2022)
A morphological study on two species of Canthon which show different nesting behaviour was carried out. The study was done on testis, accesory glands and its reservoir, corpora allata and pars intercerebralis during hatching, feeding, nest-building, nest-care and the final stage of reproduction. To each one of the different periods corresponded a physiological condition of the organs studied as well as a particular behaviour. These results suggest that the glandular activity is under control of the corpora allata which is itself regulated by the pars intercerebralis. Modification observed on the testis canot be related to change in corpora allata nor changes in pars intercerebralis.